Bridging the Green Economy and Accounting: A Path Toward Sustainable Practices - Nurul Aisyah Rachmawati (Universitas Budi Luhur, 2026)
This study examines how green economic principles can serve as a bridge to sustainable accounting practices. As the global economic system shifts toward an environmentally responsible model, conventional accounting is increasingly criticized for its inability to internalize ecological impacts and sustainability-related risks. Through a conceptual literature review supported by qualitative thematic analysis, this study explores how green economic principles can serve as a foundation for transforming traditional accounting frameworks. The findings suggest that green economics provides key conceptual orientations—such as low-carbon development, resource efficiency, and ecological stewardship—that can inform the development of sustainability-oriented accounting. Overall, this study contributes to the theoretical advancement of green accounting and underscores the importance of integrating economic and environmental perspectives to develop more sustainable accounting practices.